INOVASI DALAM RISET AKADEMIK: STRATEGI MENINGKATKAN KUALITAS DAN RELEVANSI PENELITIAN PERGURUAN TINGGI - Abrar, Muhammad (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT Academic research serves as the fundamental basis for the advancement of science and technology. However, many research outcomes produced by universities in Indonesia have yet to make a significant impact on solving real-world societal problems. This study aims to identify and analyze effective strategies to strengthen the downstream implementation (hilirisasi) of research results in Indonesian higher education institutions. The research focuses on five key strategies: strengthening collaboration and partnerships, digitalization and technology utilization, development of research infrastructure and ecosystems, capacity building of human resources, and reform of research management systems. A qualitative approach was employed, using data collection techniques such as recent literature reviews, institutional document analysis, and in-depth interviews with key informants from universities, industries, and government agencies. The findings indicate that cross-sectoral integration through programs like Kedaireka and international collaborations significantly enhance the relevance and societal acceptance of research. The use of digital technologies, such as big data and AI, accelerates research processes and broadens collaborative networks. Moreover, infrastructure such as Science and Technology Parks (STPs), capacity building through the MBKM program, and the implementation of key performance indicators (KPIs) have proven effective in strengthening the national research system. This study recommends the formulation of integrated policies and sustained investment across these five areas to accelerate impactful research commercialization that supports national development. ABSTRAK Riset akademik merupakan fondasi utama dalam pengembangan ilmu pengetahuan dan teknologi. Namun, banyak hasil penelitian perguruan tinggi yang belum berdampak signifikan terhadap pemecahan masalah nyata di masyarakat. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis strategi-strategi efektif dalam memperkuat hilirisasi hasil riset di perguruan tinggi Indonesia. Fokus utama penelitian meliputi lima strategi kunci: penguatan kolaborasi dan kemitraan, digitalisasi dan pemanfaatan teknologi, pengembangan infrastruktur dan ekosistem riset, peningkatan kapasitas sumber daya manusia, serta reformasi sistem manajemen riset. Metode yang digunakan adalah pendekatan kualitatif dengan teknik pengumpulan data berupa studi literatur terkini, analisis dokumen kelembagaan, dan wawancara mendalam dengan informan dari perguruan tinggi, industri, dan lembaga pemerintah. Hasil penelitian menunjukkan bahwa integrasi antarsektor melalui program seperti Kedaireka dan kolaborasi internasional mampu meningkatkan relevansi dan keberterimaan hasil riset di masyarakat. Pemanfaatan teknologi digital seperti big data dan AI mempercepat proses riset dan memperluas jaringan kolaboratif. Selain itu, infrastruktur seperti Science and Technology Park (STP), peningkatan kompetensi dosen dan mahasiswa melalui MBKM, serta penerapan indikator kinerja utama (IKU) terbukti memperkuat sistem riset nasional. Penelitian ini menyarankan perlunya kebijakan terintegrasi dan investasi berkelanjutan dalam kelima aspek tersebut guna mempercepat hilirisasi riset yang berdampak langsung pada pembangunan nasional.